Free-living competitive racewalkers and runners with energy availability estimates of <35 kcal·kg fat-free mass−1·day−1 exhibit peak serum progesterone concentrations indicative of ovulatory disturbances: a pilot study - Castellanos-Mendoza, M. Carolina; Galloway, Stuart D. R.; Witard, Oliver C. (Frontiers in Sports and Active Living, 2023)
The release of luteinizing hormone (LH) before ovulation is disrupted during a state of low energy availability (EA). However, it remains unknown whether a threshold EA exists in athletic populations to trigger ovulatory disturbances (anovulation and luteal phase deficiency) as indicated by peak/mid-luteal serum progesterone concentration (Pk-PRG) during the menstrual cycle. We assessed EA and Pk-PRG in 15 menstrual cycles to investigate the relationship between EA and Pk-PRG in free-living, competitive (trained-elite) Guatemalan racewalkers (n=8) and runners (n=7) [aged: 20 (14-41) years; post-menarche: 5 (2-26) years; height: 1.53±0.09 m; mass: 49±6 kg (41±5 kg fat-free ‘FFM’)]. EA was estimated over 7 consecutive days within the follicular phase using food, training, and physical activity diaries. A fasted blood sample was collected during the Pk-PRG period, 6-8 days after the LH peak, but before the final 2 days of each cycle. Serum progesterone concentration was quantified by electrochemiluminescence immunoassay. Participants that reported an EA of <35 kcal·kg FFM-1·day-1 (n=7) exhibited ovulatory disturbances (Pk-PRG ≤9.40 ng·mL-1). Athletes with EA ≥36 kcal·kg FFM-1·day-1 (n=8) recorded ‘normal’/‘potentially fertile’ cycles (Pk-PRG >9.40 ng·mL-1), except for a single racewalker with the lowest reported protein intake (1.1 g·kg body mass-1·day-1). EA was positively associated with Pk-PRG [r(9)=0.79, 95%CI: 0.37-0.94; p=0.003; 1-β=0.99] after excluding participants (n=4) that likely under-reported/reduced their dietary intake. Linear regression analysis suggests an EA ≥36 kcal·kg FFM-1·day-1 is required to achieve ‘normal ovulation’. The threshold EA associated with ovulatory disturbances in athletes and non-invasive means of monitoring the ovulatory status warrant further research.